Workplace Stress among Nurses - Mohammed, Alqahtani Ibtesam (International Journal of Innovative Research in Medical Science, 2019)
Worldwide, occupational stress among care professionals, nurses in particular, is a major concern in health care systems. Work stress in nursing is linked to high rates of job dissatisfaction, burnout, absenteeism, turnover, and stress-related illness, thus placing job performance among nurses’ and patients’ lives at risk. The purpose of this integrative review is to explore the concepts of occupational stress among nurses. Three main theoretical models are included to illustrate different viewpoints of occupational stress. Meta-analysis of the basic literature and the results of previous research are used. Findings from studies have shown that evaluations of nursing work environments reflect a strong link with burnout. The excessive workload of nursing professionals, complexity of patient care activities, poor organized work environments, and lack of leaders’ support are considered as contributing factor to the job stress which has resulted in providing unsafe care. The findings highlight that nurses frequently experience occupational stress due to the nature of the nursing profession. Thus, it is critical to implement effective organizational interventions to minimize work-related stressors and work performance of nurses. It is significant to have supportive working environments that encourage collaboration and empower nurses to provide excellent care and reduce work-related stressors.